Insemination of bocachico fish (Prochilodus magdalenae) with fresh or cryopreserved semen: effect of spermatozoa/oocyte ratio - Atencio García Víctor J; Espinosa José A; Martínez José G; Pardo Carrasco, Sandra C (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: cryopreservation is an important biotechnological tool in the conservation of biodiversity, particularly for endangered species. Objective: to evaluate six different spermatozoa/oocyte ratios using fresh and cryopreserved semen in bocachico fish (Prochilodus magdalenae). Methods: fresh semen was collected and its quality determined to verify cryopreservation feasibility. The semen was put in 5 ml straws and mixed with a solution (5.5% glucose, 12% egg yolk, and 10% dimethyl sulfoxide -DMSO-) in a 1:4 dilution (semen:solution). The semen was frozen in nitrogen vapor dry shipper for 30 min, rapidly transferred to storage thermos, and submerged directly into liquid nitrogen (LN; -196 °C). Straws were thawed at 60 ºC for 45 seconds. Motility, velocity, and sperm progressivity of fresh and cryopreserved semen were assessed using Sperm Class Analyzer (SCA®) software. Each proportion of spermatozoa/oocyte was assessed with 2 g of eggs (1,630 ± 87 eggs/g) to evaluate fertility (F), hatching (H), and larval survival (LS) rates. Results: the best reproductive performance for fresh semen was obtained inseminating with 160,000 spermatozoa/oocyte (F = 75.0%, H = 67.7%, LS = 32.7%). Similarly, the best reproductive performance for cryopreserved semen was achieved with 320,000 spermatozoa/oocyte (F = 70.0%, H = 48.6%, LS = 19.5%). Conclusion: it is possible to achieve adequate reproductive performance in bocachico fish using cryopreserved sperm (10% DMSO, 5.5% glucose, and 12% egg yolk) at twice the spermatozoa/oocyte ratio used with fresh semen.